Immunological Properties of Murine Parthenogenetic Stem Cells and Their Differentiation Products - Johannsen, Hannah; Muppala, Vijayakumar; Gröschel, Carina; Monecke, Sebastian; Elsner, Leslie; Didié, Michael; Zimmermann, Wolfram-Hubertus; Dressel, Ralf (Frontiers in Immunology, 2017)
The perspective to transplant grafts derived from pluripotent stem cells has gained much attention in recent years. Parthenogenetic stem cells (PSCs) are an alternative pluripotent stem cell type that is attractive as source of grafts for allogeneic transplantations because most PSCs are haploidentical for the major histocompatibility complex (MHC). This reduced immunogenetic complexity of PSCs could tremendously simplify the search for MHC-matched allogeneic stem cells. In this study, we have characterized immunological properties of the MHC haploidentical PSC line A3 (H2d/d) and the heterologous PSC line A6 (H2b/d). Both PSC lines largely lack MHC class I molecules, which present peptides to cytotoxic T lymphocytes (CTLs) and serve as ligands for inhibitory natural killer (NK) receptors. They express ligands for activating NK receptors, including the NKG2D ligand RAE-1, and the DNAM-1 ligands CD112 and CD155. Consequently, both PSC lines are highly susceptible to killing by IL-2-activated NK cells. In vitro-differentiated cells acquire resistance and downregulate ligands for activating NK receptors but fail to upregulate MHC class I molecules. The PSC line A6 and differentiated A6 cells are largely resistant to CTLs derived from T cell receptor transgenic OT-I mice after pulsing of the targets with the appropriate peptide. The high susceptibility to killing by activated NK cells may constitute a general feature of pluripotent stem cells as it has been also found with other pluripotent stem cell types. This activity potentially increases the safety of transplantations, if grafts contain traces of undifferentiated cells that could be tumorigenic in the recipient.